Analisis Kinerja Pegawai Dinas Ketahanan Pangan Kabupaten Ogan Komering Ulu - Tara Merlenda; Tati Herlina (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2021)
This study aims to analyze the effect of workload and work motivation on the performance of employees of the Food Security Service of Ogan Komering Ulu Regency. The sample of this research is all Civil Servants of the Food Security Service of Ogan Komering Ulu Regency, totaling 32 people. The analytical method used is a quantitative method using multiple linear regression analysis using validity and reliability tests as well as T test and F test. This study found that workload (X1) and work motivation (X2) had a significant effect on employee performance (Y), Â either partially or simultaneously. The most influential variable in this research is workload. R Square value of 0.997 can be seen that the percentage contribution of the influence of workload and work motivation on employee performance is 99.7%.